Long jump pushing-out biodynamic characteristics’ perfection - Яворська, Т. (Slobozhanskyi Herald of Science and Sport, 2011)
Among the ways that allow to build a movement on the part of its internal contents, the most promising way is the use of artificial muscle activation directly during the long jump. Attention to this area due to the presence of large reserves, which opened in the application of new instructional techniques aimed at leading athletes in the top results by creating artificial conditions.